The Effectiveness of Behavioral Group Counseling with a Modeling Technique to Improve Students Social Interaction Skills and Empathy - Jannah.B, Miftahul; Anwar Sutoyo; Mungin Eddy Wibowo (Jurnal Bimbingan Konseling, 2024)
Low social interaction skills and empathy can potentially raise problems in students. Therefore, this research aimed to analyze the effectiveness of behavioral group counseling with a modeling technique to improve students' social interaction skills and empathy at MAN 1 Palu. It used a pretest-posttest control group design in an experiment. In sampling, this research used a purposive sampling technique, while the data collection was done using the social interaction ability scale and empathy scale. Following the data collection, hypothesis testing was carried out based on the Wilcoxon sign rank test, the Mann Whitney test and the N-gain score test. According to the Wilcoxon sign rank test and Mann Whitney analysis, there was an increase in social interaction skills and empathy in the modeling group, while in the control group was no. It has proved that the behavioral group counseling with a modeling technique has been able to improve the social interaction skills and empathy of MAN 1 Palu students. Further research implications are discussed in the discussion section.